SUBSTANTIATION OF THE APPROACH TO TRANSFORMATION AND CODING TECHNOLOGY IN VIDEO IMAGE HIDING AND COMPRESSION SYSTEMS - Toliupa, Sergii; Nakonechnyi, Volodymyr; Pliushch, Oleksandr; Vedmid, Oleh; Sinenko, Dmytro (Science-based technologies, 2025)
It is clear that classical compression methods implemented on the JPEG platform do not improve the saturation level of the image. An explanation is given for the duration of the hourly costs and the pressure coefficient for the correlation stage of the image elements. To increase the efficiency of the compression technology, it is necessary to change the robot stage of reorganizing the image elements from the space-hour area into the spectral-frequency area. It is lined that directly with further advanced technology, the image is pressed in the increased potential to change the required time to the new orthogonal transformation before the hour of image processing. It is confirmed that when processing highly saturated images with piecewise constant functions, there is a change in the number of arithmetic operations in equalization with sine-cosine transformations. Systems of analytical expressions have been created that practically allow one to measure the values ​​of the characteristics of technical features, for which the hourly costs for orthogonal transformation of piecewise functions will be less than similar costs, rather than stagnation of the original methods What will happen on the sine-cosine conversion. The minimum gain per hour of processing for orthogonal transformation by piecewise constant functions and sine-cosine transformation in the average is 3.6 and 2.75 times similar for the size of the processed block. Such a game of reasoning is due to the fact that the values ​​of the matrix elements are based on piecewise constant functions and are integer numbers that take values ​​1 and -1. Therefore, the transformation is based only on integer arithmetic operations. The technology of approximation of image elements by piecewise constant functions has been proposed and has the potential to change the processing time of orthogonal transformation in image compression technology. In this case, the technology has sufficient power due to the technological complexity with the peculiarities of image processing based on the JPEG platform. Practical research to ensure that the required level of visual strength is achieved after decompression.